Phase behavior and morphological studies of polyimide/PVP/solvent/water systems by phase inversion - Kim, JH; Min, BR; Park, HC; Won, J; Kang, YS (JOHN WILEY & SONS INC, 2001)
The solubility gaps for poly(vinyl pyrrolidone) (PVP) in four polyimide solutions (NMP, DMF, GEL, DMSO) were determined by cloud point measurement and correlated with chi (PI/Solvent) and Delta delta (PVP/Solvent). Membranes prepared with NMP and DMF systems showed a tendency of suppressing fingerlike structure with addition of PVP. On the other hand, membranes prepared with GEL and DMSO systems showed an inclination toward inducing macrovoid formation. These effects of PVP on the membrane morphology were explained by means of miscibility gap, viscosity of the polymer solution, polymer-polymer phase separation, and overall porosity. (C) 2001 John Wiley & Sons, Inc.
Keywords: MEMBRANE FORMATION; IMMERSION PRECIPITATION; MECHANISM; SOLVENT; MICROSTRUCTURES; THERMODYNAMICS; SEPARATION; MACROVOIDS; ADDITIVES; ACETATE